Molecular Identification of Nontuberculous Mycobacteria from Clinical Sources by hsp65 PRA and Sequence Analysis - Ong, Chia Sui; Ngeow, Yun Fong; Yap, Sook Fan; Tay, S. T. (International Society for Infectious Diseases, 2008)
Identification of nontuberculous mycobacteria (NTM) species is becoming increasingly important as differences in antimicrobial susceptibility of these microorganisms may affect treatment options. In this study, PCR-RFLP analysis (PRA) of the gene encoding 65-kD heat shock protein (hsp65) was used for identification of 70 clinical NTM isolates obtained from two mycobacteriology laboratories in Malaysia. Approximately one third of the isolates were identified as M. fortuitum. A total of 24.3% and 10% of the isolates were identified as M. abscessus and M. avium complex respectively. Other isolates identified were M. kansasii, M. marinum, M. simiae, M. parascrofulaceum, M. szulgai, and M. gordonae. Six clinical isolates were untypable by this approach. Sequence analysis of the 439-bp region of the hsp65 gene and a 564-bp region of the 16S rRNA gene revealed high degrees (97%–100%) of sequence similarity of these isolates with “M. insubricum”, M. terrae, M. senegalense/M. conceptionense and M. houstonense in the public sequence databases. This study reported the identification of mycobacteria species which are considered rare or new to this region. As NTM are found widely in the environment, the clinical significance of the isolates in this study is yet to be determined.